Estudos ecogenômicos e bioprospectivos de Shewanella spp - Silva, Amanda Lys dos Santos (2009)
Bacteria trom Shewanella and Geobacter ganera are the most studied iron-reducing microorganisms particularly due to their electron transport systems and contribution to some industrial and environmental problems, including steel corrosion, bioenergy and bioremediation of petroleum-impacted sites. The present study was focused in two ways: the first is an in silico comparative ecogenomic study of Shewanella spp. with sequenced genomes, and the second is an experimental metagenomic work to detect iron-reducing Shewanella through PCR-DGGE of a metabolic gene. The in silico study resulted in positive correIation between copy number of 16S rDNA and genome size in Shewanella spp., with clusters of rrn near lhe origin of replication. This way, the genus is inferred as opportunist. There are no compact genomes and their sequences length varied, ranging from 4306142 nt in S. amazonensis SB2B to 5935403 nt in S. woodyi ATCC 51908, without correIation to temperature range characteristic of each specie. Intragenomic 16S rDNA sequences possess little divergence, but reasonable to resuIt in different phyIogenetic trees, depending on the sequence that is chosen to compare. For moIecuIar detection of iron-reducing Shewanella, it is proposed the mtrB gene as new biomarker. because it codes to a fundamental protein at Fe (III)-reduction. The specific primers were designed and evaluated in silico and resulted in a fragment of 360 pb. In the second study, these primers were tested in a genomic sample from S. oneidensis MR-1, amplifying the expected region. After this successfuI resuIt, the primer set was used as a tool to assess the iron-reducing communities of ShewaneIla genus under an environmental stress, i.e. crude oil contamination in mangrove sediment in Rio Grande do Norte State (Brazil). The primers presented high specificity and the reactions performed resulted in one single band of ampIification in the metagenomic samples. The fingerprinting obtained at DGGE reveaIed temporal variation of Shewanella spp. in analyzed samples. The resuIts presented show the detection of a biotechnological important group of microorganisms, the iron-reducing Shewanella spp. using a metabolic gane as target. It is concluded there are eight or more 16S rDNA sequences in Shewanella genus, with little divergence among them that affects the phylogeny; the pair of primers designed to ampIify mtrB sequences is a viable alternative to detect iron-reducing ShewanelIa in metagenomic approaches; such bacteria are present in the mangrove sediment anaIyzed, with temporal variations in the samples. This is the first experimental study that screened the iron-reducing Shewanella genus in a metagenomic experiment of mangrove sediments subjected to oil contamination through a key metabolic gene